Achieving safer Ramadan fasting by keeping flexible glycemic targets during the day and tighter targets during the night in insulin treated people with type 2 diabetes. (July 2020) - Ahmedani, Muhammad Yakoob; Ghafoor, Erum
Abstract: Aim: To observe the effect of keeping flexible glycemic targets during fasting and tighter targets during non-fasting hours in insulin-treated people with type 2 diabetes during Ramadan. Methods: This prospective study was conducted at Baqai Institute of Diabetology and Endocrinology in 2014. People with T2DM on split mixed insulin therapy were recruited. The pre-Ramadan education given and insulin doses were adjusted before Ramadan. 24-hour telephonic helpline service was provided to achieve pre-determined glycemic targets and minimize complications. Results: A total of 54 people with T2DM with a mean age of 54.65 ± 9.32 years were recruited. Mean glucose levels achieved were 183.50 ± 30.91 mg/dl and 179.20 ± 36.27 mg/dl during the day and night respectively. Mean HbA1c (p-value < 0.0001) and serum creatinine (p-value 0.0010) significantly improved at the end of Ramadan. 0.6% episodes of hypoglycemia including one major hypoglycemia while 30% of episodes of hyperglycemia were recorded. No hospitalization needed. Conclusion: By keeping flexible glycemic targets during the day and tighter targets during the night, safe fasting was feasible with significant improvement in overall glycemic control without significant major complications.